2022
DOI: 10.4266/acc.2022.00542
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein-to-albumin ratio and 6-month mortality in out-of-hospital cardiac arrest

Abstract: Background:The inflammatory response that occurs following cardiac arrest can determine the long-term prognosis of patients who survive out-of-hospital cardiac arrest. We evaluated the correlation between C-reactive protein-to-albumin ratio (CAR) following cardiac arrest and long-term mortality. Methods:The current retrospective observational study examined patients with post-cardiac arrest syndrome (PCAS) treated with targeted temperature management at a single tertiary care hospital. We measured CAR at four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Previous studies have investigated the predictive performance of several biomarkers in the prognosis of sepsis patients, including platelet 26 , neutrophil/lymphocyte ratio (NLR) 27 , lactate/albumin ratio 28 , plasminogen activator inhibitor-1 (PAI-1) 29 , signal peptide-CUB-epidermal growth factor-like domain-containing protein 1 (SCUBE-1) 30 , and vitamin D receptor 31 . CAR has been recently used as a new prognostic marker in COVID-19 32 , severe fever with thrombocytopenia syndrome (SFTS) 33 , and cardiac arrest 34 . However, the predictive performance of CAR in the prognosis of sepsis patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the predictive performance of several biomarkers in the prognosis of sepsis patients, including platelet 26 , neutrophil/lymphocyte ratio (NLR) 27 , lactate/albumin ratio 28 , plasminogen activator inhibitor-1 (PAI-1) 29 , signal peptide-CUB-epidermal growth factor-like domain-containing protein 1 (SCUBE-1) 30 , and vitamin D receptor 31 . CAR has been recently used as a new prognostic marker in COVID-19 32 , severe fever with thrombocytopenia syndrome (SFTS) 33 , and cardiac arrest 34 . However, the predictive performance of CAR in the prognosis of sepsis patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an acute-phase protein released by hepatocytes, where its transcription is induced mainly by IL-6 and IL-1β. 41 Thirteen individual studies with a total of 3005 patients evaluated CRP as a prognostic marker, 12,13,16,20,21,25,27,33,[42][43][44][45][46][47] and four studies with 792 patients assessed high-sensitivity CRP (hsCRP). 19,39,48,49 While conventional CRP assays have a detection limit of 3 to 8 mg/L, hsCRP assays can detect CRP levels as low as 0.3 mg/L.…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…21,46 Gregers et al reported that lower CRP levels at admission and on day one independently predict poor neurological outcome at hospital discharge in a study where all patients underwent extracorporeal cardiopulmonary resuscitation. 45 Studies on later time points reported conflicting results: Kim et al reported unadjusted association with outcome on days one to three, 44 an independent association on day two, 16,48,49 whereas three studies found no association at any time point. 12,13,19,47 Most of these studies also reported negative results for other time points.…”
Section: C-reactive Proteinmentioning
confidence: 99%
See 2 more Smart Citations